Seasonal Particle Size Distribution and its Influencing Factors in a Typical Polluted City in North China - Wenxin Wang; Xiaohua Wang; Xue Li; Chao Chen; Yu Wang; Zhiwen Xing; Kun Li; Min Wei; Xiao Sui; Houfeng Liu (Aerosol and Air Quality Research)
Abstract In this study, the particle size distribution and its influencing factors were conducted using a multi-channel particle size sensor coupled with Pearson and generalized additive model (GAM) during winter 2021 to autumn 2022 in Jinan, North China. The results revealed that heavy pollution episodes were mainly caused by fine particles (PM<1 and PM1-2.5) in winter and coarse particles (PM2.5-10 and PM>10) in spring. Pearson and generalized additive model (GAM) analysis indicated PM2.5 was positively correlated with relative humidity (RH), CO, NO2, SO2, and PM2.5-10 concentrations, negatively correlated with wind speed, O3 and coarse particles (PM>10) concentrations. Moreover, there was also a strong correlation between PM2.5 concentration and meteorological-air pollutant factors interactions. PM2.5-10 was found to be positively correlated with gaseous pollutants such as NO2, SO2, and CO, as well as RH and air pressure. Besides, PM>10 was positively associated with CO, SO2, and RH, but negatively correlated with NO2 and wind speed. The particle size distribution was also effected by regional transport, particular in winter and spring. In detail, PM2.5 and PM2.5-10 were mainly transported from the east and north, PM>10 mainly from the north and southwest in winter. In spring, particle matters were mainly transported from the northeast and southeast, and PM2.5 was more influenced by northeast short-range transport. Local particulate generation was mainly raised by mobile sources from vehicles and industries such as oil refineries, chemical plant and steel plants. Therefore, the emission controls on VOCs, NO2, SO2 and regional joint pollution prevention are preferred to reduce urban air pollution in future.